Liability for Nuclear Damage: Lessons from the Nuclear Reactor Damage Tragedy at Fukushima Daiichi, Japan: (Liabiliti Akibat Kerosakan Reaktor Nuklear: Iktibar daripada Tragedi Fukushima Daiichi) (Kanun: Jurnal Undang-undang Malaysia, 2017)
This article explicates the legal issues and liabilities related to the nuclear damage at Fukushima, Japan in the hope it will provide lessons to Malaysia in handling any nuclear-related damage in the future. In addition, this paper also reviews the international laws pertaining to claims for compensation and protection to victims and property as well as the international standards with regard to compensation payments to victims. It is hoped that this will give a clear picture of the laws and liabilities that the Government should undertake in providing adequate protection in case of a nuclear-related disaster in Malaysia.Keywords: liability, nuclear damage, nuclear energy, international, law, nuclear law.